KIAI INTERPERSONAL MANAGERIAL: HENRY MINTZBERG PERSPECTIVE - Abdul Karim; Dikhorir Afnan (Universitas Gadjah Mada, 2020)
The applicative theory used as a supporting statement is the concept of Henry Mintzberg's interpersonal managerial role. It is undeniable to see the gap between management theory and the concept of social interaction in Islam. The term defined by some experts is bounded value, individual, and nonexclusive. The theory emphasizes more on the system through management functions, whereas in Islam, the leadership figures are more desirable. This study answers, how is the application of interpersonal managerial roles in the Al-Ishlah Islamic Boarding School from Henry Mintzberg's perspective? The method used in this study is qualitative research with observation and interview instruments as tools of data collection. From the results of data collection, researchers conducted descriptive analysis steps namely categorization, reduction, and interpretation. The results show that Kiai's interpersonal managerial role forms as: first, Kiai al-Ishlah figure, and the ceremonial stage of the leadership. Second, the pattern of the al-Ishlah Islamic boarding school organization, personal improvement, independence, productivity, and special training. Third, educational cooperation and equality cooperation. The implication is that it is understandable that management theory is not the main theory used in an Islamic boarding school because the managerial role of Kiai managerial firmly determines the pace of Islamic boarding school management